Classification Techniques in Analysis of Salem District Soil condition for Cultivation of Sunflower - Hemageetha, N; Nagalakshmi, N (International Journal of Computer Sciences and Engineering, 2025)
Agriculture is the backbone of Indian economy. Sunflower is one of the most important oil seed crops grown in temperate countries and India is one of the largest producers of oil seeds in the world. The farmers can determine which type of crops to be cultivated in a particular place with the help of the soil condition analysis. The valuable knowledge is extracted from the agricultural data set with the help of data mining techniques. The farmers can make use of the technology and the right techniques; they can make agriculture a profitable enterprise. Salem district is one of the largest districts in Tamil Nadu, India and it is famous for mango cultivation This paper analyzes whether the Salem district soil is suitable for the cultivation of sunflower crop with the help of data mining classification techniques